A STRUCTURE-INDEPENDENT DATA AGGREGATION MECHANISM FOR WIRELESS SENSOR NETWORKS - AGARWAL, SHOBHIT (2014)
Wireless Sensor Networks (WSNs) aim at providing distributed and real-time information about the physical world in an efficient manner. The limiting factors for energy efficient data gathering in WSNs are redundancy in sensed data, dynamic network topology and global information inaccessibility. Data aggregation offers a key solution to curtail the network load and reduce data transmissions, thereby improving energy efficiency of WSNs. Many data aggregation protocols have been proposed for WSNs. However, current state of the art techniques focus on computing and maintaining a fixed network structure for efficient aggregation, which leads to high maintenance overheads.